Pragilling Cooling Technique on Quality Characteristics of Milled Rice based on Cooling Temperature and Duration (AGARICUS: Advances Agriculture Science & Farming, 2022)
This  study  aims  to determine  the  effect  of  temperature,  duration  of  cooling,  and  physical  quality  of  rice  that is influenced  by  pragiling  refrigeration  technique.  The  resultsshowed  a  decrease  of  moisture content in  the  process  of  drying  of  impari  varieties  (22.4% -13.4%)  and  cisadane  varieties (25% -14.3%). Dry shrinkage occurs due to the amount of water that evaporates during the drying process on the 16 kg varieties of impari and cisadane varieties of 21 kg. In addition to the varieties of grain milled rice varieties also affected by the characteristics of grain quality, the varieties of impari obtained average (52.40 Â± 3.23%) while in cisadane varieties obtained average (54.54 Â± 1.2%). Visual appearance, color degree measurement (Lab *) of milled rice with  pragiling  and  non  cooling  cooling  technique  has  no  significant  effect  on  the  given treatment. In the analysis of quality characteristics of rice with pragiling cooling technique, the  quality  of  rice  produced  is  better  than  non-coolant  treatment  this  is  seen  from  the percentage of head grains, broken grains and groats that produced reached 87.68%. This is in  accordance  with  the  analysis  data  of  variance  where  temperature  has  significant  effect (0.00